2015
DOI: 10.1265/jjh.70.211
|View full text |Cite
|
Sign up to set email alerts
|

Recent Knowledge of Smoking and Peripheral Arterial Disease in Lower Extremities

Abstract: Peripheral arterial disease (PAD) is an atherosclerotic obstructive disease of the arteries in lower extremities. Patients with PAD show high rates of mortality from coronary artery disease (CAD) and stroke. Smoking as well as diabetes is an important risk factor for PAD. A lesion of PAD in the lower extremities tends to be more proximal in smokers than in nonsmokers and to be more distal in patients with diabetes than in nondiabetics. By a systematic review, the odds ratio for PAD of smokers vs nonsmokers has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 43 publications
0
5
0
6
Order By: Relevance
“…Ostchega et al identifi ed current smoking, previous smoking, diabetes mellitus, not controlled or untreated hypertension as signifi cant risk factors associated with PAOD in persons aged 60 and older. 16 Sotoda et al reported an odds ratio for PAOD of smokers versus non-smokers that range from 1.7 to 7.4 17 , while Lu at al. reported that there is a substantial evidence of an association between active smoking and PAOD 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Ostchega et al identifi ed current smoking, previous smoking, diabetes mellitus, not controlled or untreated hypertension as signifi cant risk factors associated with PAOD in persons aged 60 and older. 16 Sotoda et al reported an odds ratio for PAOD of smokers versus non-smokers that range from 1.7 to 7.4 17 , while Lu at al. reported that there is a substantial evidence of an association between active smoking and PAOD 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Полученные в представленном исследовании результаты свидетельствуют о более высоких уровнях маркеров ЭД на фоне курения, имеют подтверждение в литературе [6][7][8][9][10][11][12]. В частности, в исследовании [6] выявлено увеличение уровня эндотелиальных клеток-предшественниц в крови как активных, так и пассивных курильщиков, что косвенно согласуется с полученными в настоящем исследовании результатами более высоких уровнях NO x у курящих пациентов, и позволяет предполагать наличие нарастания окислительных процессов на этапах формирования ЭД у больных ГБ под воздействием курения.…”
Section: Discussionunclassified
“…Полученные в исследовании данные о более высоких средних концентрациях Э-1 [7], Гц [9,10], ФфВ [11,12] и тПА [11,12] у курящих больных ГБ также не противоречат результатам других исследователей и отражают формирование ЭД с возможным прогрессированием поражения микроциркуляторного русла не только у больных ГБ, но и "здоровых" курильщиков.…”
Section: Discussionunclassified
See 2 more Smart Citations